2009
DOI: 10.1007/s11270-009-0213-7
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Record of Lead Contamination in Alluvial Soils and Tree Rings on Recent Floodplains (Southern Québec, Canada)

Abstract: Current and past industrial pollution leaves many traces in the environment, in particular along rivers in industrial and urban areas. The isotopic analysis of the lead found in soils and tree rings offers a kind of environmental archive for presenting a portrait of the pollutant distribution in the environment in both spatial and temporal terms. This study is an attempt to identify and compare the source of contamination found in soils and tree rings located along two rivers affected by pollution over several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
(54 reference statements)
1
18
0
Order By: Relevance
“…Also, the Pb isotope composition obtained using on the geochemical analyses of the Pb detected in the rings of tree specimens (Red ash /Fraxinus pennsylvanica) in the same study areas leads us to believe that there were two or three discharges of oil into the river (St-Laurent et al, 2009). These spills appear to have likely occurred between 1948 and 1968 according to our dendrogeochemical analyses performed on specimens of trees found along the riverbanks (Saint-Laurent et al, 2010b). Note that Pb was still being added to gasoline during this time, and it was only later (i.e., in 1990) that the Government of Canada prohibited its use (CEPA, 1990;Health Canada, 2009).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Also, the Pb isotope composition obtained using on the geochemical analyses of the Pb detected in the rings of tree specimens (Red ash /Fraxinus pennsylvanica) in the same study areas leads us to believe that there were two or three discharges of oil into the river (St-Laurent et al, 2009). These spills appear to have likely occurred between 1948 and 1968 according to our dendrogeochemical analyses performed on specimens of trees found along the riverbanks (Saint-Laurent et al, 2010b). Note that Pb was still being added to gasoline during this time, and it was only later (i.e., in 1990) that the Government of Canada prohibited its use (CEPA, 1990;Health Canada, 2009).…”
Section: Introductionmentioning
confidence: 88%
“…Our previous work conducted on hydrocarbon-contamined layers found in alluvial soils (Saint-Laurent et al, 2008;2010a;2010b) showed marked differences in the Pb isotope values (e.g., 206 Pb/ 207 Pb, 208 Pb/ 206 Pb), suggesting separate spills of petroleum products in the rivers. For instance, the values obtained for Pb isotope ratios 206 Pb/ 207 Pb ranged from 0.124 to 0.175 ± 0.01 SD (Saint-Laurent et al, 2010b;2010c).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In short, overly frequent flooding can disrupt pedogenetic processes and hinder biogeochemical cycles and the development of riparian stands (Franklin et al 2009;Hamdan et al 2010). Also, flood frequency leads to fine sediments being continuously deposited on floodplains, and some of these sediments may contain contaminants such as heavy metals and pollutants (Macklin et al 2006;Saint-Laurent et al 2009;Bird et al 2010;Saint-Laurent et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Aznar et al, 2008;Kirchner et al, 2008;Lageard et al, 2008;Saint-Laurent et al, 2010;Wu et al, 2010;Mihaljevič et al, 2011 andZuna et al, 2011). These methods offer multi-element and isotope analysis with low detection limits, but relatively large amounts of wood sample are needed.…”
Section: Introductionmentioning
confidence: 99%